Appropriate model for landfill rehabilitation in India using hazard rating system. Issue 2 (21st January 2019) - Naveen, BP; Goel, Apoorva
Abstract : Unscientific and imprudent approaches to solid waste management have created large waste sites that pollute groundwater, soil and air and endanger public health. However, remediation of landfill sites is a major challenge for developing countries such as India due to financial constraints and accelerating waste generation rate. Achieving the most effective resource allocation in the face of these challenges entails a hazard-based prioritisation list of landfills through multiple hazard pathways. Hazard rating systems that generate such lists are being widely employed by developed countries around the world. However, they lack pertinent parameters and the ability to characterise a wide array of hazard levels in landfills found in many developing countries. This paper investigates existing hazard rating models and landfill sites and sets forth a cost-effective hazard rating system that can identify a wide array of hazard levels in landfills found in geographically and economically extreme regions. The proposed model, hazard decision model (HDM), is a relative hazard assessment model, based on source–pathway–receptor relationships, that computes hazard scores for groundwater, direct contact and risk of fire routes. It generates separate priority lists for remedial action and emergency action. HDM is compared with existing hazard rating models while they are applied to nine characteristically different Indian landfills. The results demonstrate that HDM can generate more distinguishable scores and exhibit greater sensitivity to varied landfill and receptor hazard characteristics, making it a more effective tool for site ranking and evaluating remedial strategies.